2011
DOI: 10.1097/scs.0b013e3182323cdf
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion 3q Syndrome

Abstract: The authors present the clinical case of a 5-month-old boy, affected by multimalformative syndrome with features of microdeletion 3q syndrome. In the literature so far, the real incidence is unknown because of its rarity. The goal of this study was to describe the salient findings of this rare malformative syndrome, which needs a multidisciplinary approach. The patient had 3q interstitial chromosome deletion (q22.1-q25.2). He showed the following clinical features: microcephaly, microphthalmia, epicantus inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…We performed SNP array analysis also in a 3q deleted patient with DWM and blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES), whose detailed clinical features have been recently published [8]. This patient was found to carry a 19.2 Mb deletion of the region 3q22.1q25.1, from 132381260 bp (CN_995516) to 151675126 bp (CN_998137), including the FOXL2 , ZIC1 and ZIC4 genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed SNP array analysis also in a 3q deleted patient with DWM and blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES), whose detailed clinical features have been recently published [8]. This patient was found to carry a 19.2 Mb deletion of the region 3q22.1q25.1, from 132381260 bp (CN_995516) to 151675126 bp (CN_998137), including the FOXL2 , ZIC1 and ZIC4 genes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this analysis, we propose the diagnosis of WS to be made based on the occurrence of at least four out of five core gestaltic features (coarse facies; prominent or wide triangular shaped nasal tip; high arched or upsweeping eyebrows; full/everted lower lip; bushy eyebrows often with synophrys). Accordingly, we diagnosed 12 patients with WS [6,9,22,23,25-29] and compared them with 15 patients who did not match the proposed criteria [7,8,12,16-18,30-37] (Table 1 and Additional file 1: Table S1). Among this second group, the occurrence of each gestaltic feature was much rarer than in the WS group.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure these seven patients with clinical diagnosis of WS and additional cases of 3q deletion, without a clinical diagnosis of WS are shown along with our case to aid in narrowing the WS critical region [Rea et al, ; Lim et al, ; Ramieri et al, ; Weber et al, ]. Patient 12 has a deletion that distally overlaps with ours, but apparently no clinical diagnosis of WS [Lim et al, ].…”
Section: Discussionmentioning
confidence: 72%
“…With the exception of the above patient, we suggest that the proximal breakpoint of WS critical region is given by the distal breakpoint of patient 11 [Ramieri et al, ; Ferraris et al, ] whose clinical description and the pictures reported are not reminiscent of WS. The distal one is given by the distal breakpoint of our patient.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation